Predictors of permanent pacemaker implantation in aortic valve diseases after TAVI with vitaFlow liberty system - Changlin Ju; Changlin Ju; Xiangrong Xie; Shengxin Tang; Shiping Cao (Frontiers in Cardiovascular Medicine, 2023)
IntroductionPermanent pacemaker implantation (PPI) is a known complication in patients with aortic stenosis following transcatheter aortic valve implantation (TAVI). However, there is limited research on TAVI for pure aortic regurgitation (PAR), and more investigation is needed to determine the occurrence of postoperative cardiac conduction block and the need for PPI in this population. Therefore, this retrospective analysis aimed to evaluate the incidence of cardiac conduction block and the necessity of PPI after TAVI in patients with different types of aortic valve disease, including pure aortic stenosis (PAS), aortic stenosis with regurgitation (ASR), and PAR.MethodsClinical data of 100 patients who TAVI were analyzed retrospectively. The incidence of conduction block was assessed, and clinical factors were examined to predict the necessity of PPI.ResultsCardiac conduction block was found to be a common complication following TAVI, particularly in patients with PAR. PAR was identified as an independent risk factor for requiring PPI. Additionally, first-degree atrioventricular block emerged as a sensitive predictor for PPI in patients with PAR.DiscussionThese findings provide valuable insights into the safety and effectiveness of TAVI, which can help enhance patient management and reduce complications.